Islamicisation of Medicine in the 13th Century: A Case of Ibn Abī Uṣaibia‘s History of Physicians - Abd Rahman, Akmal Khuzairy bin (IIUM Medical Journal Malaysia, 2018)
One of the challenges in the Islamization of knowledge project is the absence of a ready approach for integrating the existing disciplines within the Islamic knowledge paradigm. Among the constituents of such an approach is an epistemological framework that defines a discipline to serve as reference for further efforts on the operational level. This study intends to fill this gap with a perspective on Islamic epistemological framework in the field of medicine during the Islamic medieval era. The focus of analysis is on the topic of the origin of medicine and the views of ancient Greek physicians in the compilation entitled ‘Uyūn al-anbā’ fī ṭabaqāt al-aṭibba’ or History of Physicians authored by Ibn ’Abī ’Uṣaibia‘. The study used interpretive textual analysis method to arrive at certain constructs for an Islamic medical epistemological framework from the point of view of the author. The analysis concludes that the perspective of the author on the selected topics was suggestive of possible constructs for an Islamic epistemological framework that can serve as a point of reference for further development of an approach for integrating medical disciplines in the Islamization context.